2021
DOI: 10.1111/exd.14398
|View full text |Cite
|
Sign up to set email alerts
|

Yin and Yang: A disrupted skin microbiome and an aberrant host immune response in hidradenitis suppurativa

Abstract: Hidradenitis suppurativa (HS) is a chronic multifaceted, potentially scarring, inflammatory skin disease affecting the pilosebaceous units (PSU) of the axilla, inframammary folds, groin and buttocks. Clinical features include painful inflammatory nodules, abscesses and draining sinus tracts that produce a purulent, foul-smelling discharge. The estimated prevalence of HS is 0.2-0.6% globally, but the prevalence varies by geographic location: 0.5-1.3% in Europe, 0.7-1.2% in the United States and 0.01%-2.2% in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 218 publications
(296 reference statements)
1
19
0
1
Order By: Relevance
“…This coexistence is fundamental for the fine-tuning of the immune system and requires an intimate relation with commensal microbes, especially during early childhood [ 152 , 153 ]. Therefore, it is not surprising that alterations in these close microbiome–immunity interactions are associated with increased susceptibility to pathogenic infections, overgrowth of commensals, and their potential spread throughout the body via impaired mucosal barriers [ 154 , 155 ]. These contribute to the onset and development of several disorders, including IBD [ 45 ], rheumatic arthritis [ 156 ], neurodegenerative diseases [ 157 ], and even tumors [ 158 ].…”
Section: Beyond Prokaryotic Omics: Interactions Of the Core Human Mic...mentioning
confidence: 99%
“…This coexistence is fundamental for the fine-tuning of the immune system and requires an intimate relation with commensal microbes, especially during early childhood [ 152 , 153 ]. Therefore, it is not surprising that alterations in these close microbiome–immunity interactions are associated with increased susceptibility to pathogenic infections, overgrowth of commensals, and their potential spread throughout the body via impaired mucosal barriers [ 154 , 155 ]. These contribute to the onset and development of several disorders, including IBD [ 45 ], rheumatic arthritis [ 156 ], neurodegenerative diseases [ 157 ], and even tumors [ 158 ].…”
Section: Beyond Prokaryotic Omics: Interactions Of the Core Human Mic...mentioning
confidence: 99%
“…Although its pathogenesis is still unclear, many risk factors have been identified, including genetic predisposition, obesity, smoking habit, and hormonal disorders [ 97 ].…”
Section: Skin Aquaporins In Inflammatory Dermatological Diseasesmentioning
confidence: 99%
“…Several findings suggested that HS is associated, as other inflammatory skin diseases (including atopic dermatitis and acne vulgaris), with dysbiosis, that is an imbalance (any change to the composition) of the skin "healthy" resident microbiome. Indeed, microbial dysbiosis in HS has been the subject of over 200 publications; nevertheless, its exact role in HS pathogenesis remains elusive and is yet to be fully clarified [53]. In their recent review (which includes 21 studies examining the cutaneous microbiome), Wark and Cains reported that (i) Staphylococcus aureus, coagulase-negative staphylococci, and Enterobacteriaceae species were commonly cultured from HS skin, and (ii) Porphyromonas and Prevotella (both anaerobic bacteria) were relatively increased in HS skin, as demonstrated by 16S rRNA sequencing studies [54].…”
Section: The Role Of Cutaneous Microbiome In Hsmentioning
confidence: 99%